Viscosity measurements of poly(ethyleneglycol) 400 [PEG 400] at temperatures from 293 K to 348 K and at pressures up to 50 MPa using the vibrating wire technique - Sequeira, Maria C. M. (2019)
The article reports new measurements of the viscosity of Poly(ethyleneglycol) 400 [PEG 400] in the range (293-348) K and pressures up to 50 MPa. Complementary measurements of the density of the same sample of PEG 400 have been made covering the ranges of temperature and pressure, (293-353) K and (0.1-50) MPa, respectively. The viscosity measurements were performed using the vibrating wire technique in the forced mode of oscillation and the density measurements were carried out with an Anton Paar vibrating U-tube densimeter. The density raw data were corrected for viscosity effects. The overall uncertainty of the viscosity measurements is estimated to be less than +/- 2% for viscosities up to 68 mPa s and less than +/- 2.6% for higher viscosities. The densities have an estimated overall uncertainty of +/- 0.2%. The rheological behaviour of Poly(ethylene Glycol) 400 has also been studied, using a cone-plate Brookfield viscometer, in a temperature range between (293 and 333) K. The measurements were carried out at shear rates up to 20 s(-1) and shear stresses up to 2.20 Pa and have evidenced Newtonian behaviour. The viscosity data obtained were correlated by means of a modified hard-sphere based correlation technique. The relative root mean square, rms, deviation of the experimental results from the correlation equations is 0.54%, and their bias is practically zero. The density data obtained were correlated using a Tait-type equation. As a complement of the present study, the surface tension of PEG 400 was measured by the pendant drop method. This study aims to be useful for viscosity measurements using capillary viscometers. As far as the authors are aware, the present viscosity measurements are the first results to be published for PEG 400 at pressures higher than atmospheric pressure.